BEEF MEAT QUALITY: A REVIEW - LALA, Bruno; POSSAMAI, Ana Paula Silva; PEREIRA, Vinicius Valim; DINIZ, Paula Porcena; DA SILVA, Stefânia Caroline Claudino; GRANDE, Paula Adriana; MAC-LEAN, Priscilla Ayleen Bustos (Revista Brasileira de Engenharia de Biossistemas, 2013)
The differentiation of foods provides a better quality product to the end consumer. Increased requirement of consumers for food quality to force organizations to develop instruments with greater efficiency in security, differentiation and adding value to their products. Traceability provides the consumer, through legislation, to guarantee a product that is being tracked at all stages of the production process, allowing also return to the origins, providing useful information to correct and refine the chains. The aim of this review to address the production of meat quality critical consumer.